A case report of a sialolith proving difficult to locate, with a sudden urgency to rule out a mucoepidermoid carcinoma. (19th April 2021) - Sandhu, Baljinder Kaur; Weir, Justin; Devine, Maria
Abstract: Sialoliths arising extraductally are rarely reported, particularly when large in size. Here we report a large calcified mass presenting in the submandibular region which proved difficult to locate with imaging. Clinical presentation findings can include pain, swelling (usually associated with eating), obstruction of the salivary duct and sialadenitis. A 71‐year‐old male was referred by his general dental practitioner to the Oral Surgery department regarding a 6‐month history of a firm painful swelling in the left floor of mouth. He had experienced only one episode of associated submandibular swelling which resolved spontaneously after a few days. A large, mobile, firm mass was palpable on clinical examination in the left lingual sulcus, which was slightly tender. There was no associated swelling palpable of the submandibular gland. Ultrasound imaging confirmed a calcified mass present of 18 mm in anteroposterior (AP) dimension which was not related to the submandibular duct or gland. Following recommendation from the Radiologist, a small field computed tomography (CT) scan was requested to locate the mass and determine its relationship to adjacent structures. CT findings confirmed a heavy calcified mass replacing much of the sublingual gland, with the absence of submandibular sialadenitis or duct dilation. The report raised a query of mucoepidermoid carcinoma so prompt excision to confirm the diagnosis was arranged accordingly. The patient recovered well following extraductal excision of the sialolith and marsupialisation of the submandibular duct under general anaesthesia.